Deciphering Abiotic Influences on the Seasonal Dynamics of Leaf Folder and Caseworm Infesting Rice in the Konkan Region of Maharashtra - Nikhil Khemrajji Hatwar; Vinayak Narayan Jalgaonkar; Priti Sunil Shigwan; Kumud Vitthal Naik; Aaditya Jadhav (International Journal of Economic Plants)
Rice is an essential cereal crop and serves as the primary food source for the majority of people worldwide. It faces significant challenges from various abiotic and biotic stress factors, with insect pests being a major concern. An experiment was conducted during kharif (June–October), 2019 at Regional Agricultural Research Station (RARS), Karjat, Maharashtra, to study how abiotic factors affect the prevalence of leaf folders and caseworms in rice ecosystems. The results showed that the initial detection of rice leaf folders and caseworms occurred during the 31st Standard Meteorological Week (SMW). The highest incidence of rice leaf folders (1.04%) and caseworms (0.69%) was recorded in the 34th SMW. The minimum leaf folder infestation (0.11±0.38%) was recorded in the 40th SMW, while the minimum case worm infestation (0.09±0.25%) occurred during the 37th SMW. Correlation analysis revealed that minimum temperature significantly influenced the population of both the pests. Regression analysis demonstrated that maximum temperature and bright sunshine hours accounted for R2=0.865 of the variability in the leaf folder population and R2=0.798 of the variability in the caseworm population due to maximum temperature. The findings of this study hold significant implications, providing a valuable foundation for predicting pest populations and aiding in the formulation of management strategies in the Konkan region of Maharashtra.